Effect of different types of exercises on psychological and cognitive features in people with Parkinson's disease: A randomized controlled trial - Gobbi, Lilian Teresa Bucken [UNESP]; Pelicioni, Paulo Henrique Silva; Lahr, Juliana [UNESP]; Lirani-Silva, Ellen [UNESP]; Teixeira-Arroyo, Claudia; Santos, Paulo Cezar Rocha dos [UNESP] (Elsevier, 2021)
Background: Parkinson's disease (PD) is a neurodegenerative and progressive disease marked by the presence of motor and non-motor symptoms, as psychological and cognitive impairment. Physical exercises have been prescribed as complementary therapy for PD, and the type of intervention and duration of the intervention should be taken into account. Objective: We aimed to compare the effect of different exercise modalities (functional mobility, multimodal and cognitive) and length (4 and 8 months) on psychological and cognition in people with PD. This study followed the CONSORT extension for non-pharmacological trials. Methods: In this randomized controlled trial, we assessed 107 participants between 2011 and 2013. At the end of 3 years, participants with PD (mild to moderate stages) who achieved the criteria were assessed considering 3 different groups of exercise: Multimodal (n = 38), Functional Mobility (n = 33) and Mental/Leisure (n = 36). All 3 interventions were performed for 32 weeks, twice a week, with 60 min for each session (64 sessions in total). Psychological and cognitive function were assessed at baseline and after 4 and 8 months. Results: The Functional Mobility and Mental/Leisure training had a potential effect on maintaining cognitive function (executive function, attention and work memory). The Multimodal training did not show a benefit for cognitive features and was not even able to delay the progressive decline in cognitive functions; however, this modality had a positive effect on physical stress after 8 months of exercise. Conclusions: An intervention that requires high complexity and specific activities, such as locomotor and cognitive exercise, provides a maintenance effect against the degeneration in cognition associated with the progression of PD and thus can delay the progressive decline in cognitive function in PD.
Keywords: Cognition; Cognitive training; Functional mobility training.; Parkinson's disease; Physical activity